Fast motions in biomechanics and robotics: optimization and feedback control - Diehl, Moritz; Mombaur, Katja (Springer Berlin Heidelberg, 2006)
Re-injecting the Structure in NMPC Schemes Application to the Constrained Stabilization of a Snakeboard -- Recent Advances on the Algorithmic Optimization of Robot Motion -- A Spring Assisted One Degree of Freedom Climbing Model -- Fast Direct Multiple Shooting Algorithms for Optimal Robot Control -- Stability Analysis of Bipedal Walking with Control or Monitoring of the Center of Pressure -- Multi-Locomotion Control of Biped Locomotion and Brachiation Robot -- On the Determination of the Basin of Attraction for Stationary and Periodic Movements -- Task-Level Control of the Lateral Leg Spring Model of Cockroach Locomotion -- Investigating the Use of Iterative Learning Control and Repetitive Control to Implement Periodic Gaits -- Actuation System and Control Concept for a Running Biped -- Dynamical Synthesis of a Walking Cyclic Gait for a Biped with Point Feet -- Performing Open-Loop Stable Flip-Flops — An Example for Stability Optimization and Robustness Analysis of Fast Periodic Motions -- Achieving Bipedal Running with RABBIT: Six Steps Toward Infinity -- Velocity-Based Stability Margins for Fast Bipedal Walking -- Nonlinear Model Predictive Control and Sum of Squares Techniques -- Comparison of Two Measures of Dynamic Stability During Treadmill Walking -- Simple Feedback Control of Cockroach Running -- Running and Walking with Compliant Legs -- Self-stability in Biological Systems — Studies based on Biomechanical Models -- Holonomy and Nonholonomy in the Dynamics of Articulated Motion -- Dynamic Stability of a Simple Biped Walking System with Swing Leg Retraction.
Gesehen am 11.02.2013
Keywords: Robotik; Bewegungssteuerung; Regelungssystem; Biomechanik; Simulation; Bewegungsanalyse; Lernendes System; Bahnplanung; Mobiler Roboter